1965
DOI: 10.1021/ja01087a027
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin A. V. The Structure of Valine- and Isoleucine-gramicidin A

Abstract: When this hydrochloride (0.005 mmole) was dissolved in 50 ml. of 0.01 M bicarbonate (pH 8.75), the Xmax at 217 m/i (c 12,100) disappeared after 1 hr., and continuous extraction with methylene chloride gave 5,10dioxo-l,6-diazacyclodecane.Treatment of 34 mg. (0.2 mmole) of the cyclodipeptide with 10 ml. of 0.1 M carbonate solution (pH 10.7) for 3.5 hr. on the steam bath followed by continuous extraction with methylene chloride gave 22 mg. of 2-pyrrolidinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
174
0
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(177 citation statements)
references
References 4 publications
2
174
0
1
Order By: Relevance
“…These highly cytotoxic peptides -isolated from a marine sponge, but probably of microbial origin -feature two other types of non-ribosomal amino acids, i.e., d-amino acids and N-methyl amino acids, which are both known to prevent peptidase cleavage (cf. the antibiotic gramicidin A, which consists of a chain of alternating l-and d-aminoacid residues [12], or the immunosuppressive cyclic undecapeptide cyclosporin A, containing six N-methyl, and three non-proteinogenic (Bmt, Abu, d-Ala) amino acid moieties [13]). Peptides consisting entirely of d-amino acids with proteinogenic side chains are completely stable towards peptidases; they are often used to study those properties of their normal counterparts (enantiomers!…”
mentioning
confidence: 99%
“…These highly cytotoxic peptides -isolated from a marine sponge, but probably of microbial origin -feature two other types of non-ribosomal amino acids, i.e., d-amino acids and N-methyl amino acids, which are both known to prevent peptidase cleavage (cf. the antibiotic gramicidin A, which consists of a chain of alternating l-and d-aminoacid residues [12], or the immunosuppressive cyclic undecapeptide cyclosporin A, containing six N-methyl, and three non-proteinogenic (Bmt, Abu, d-Ala) amino acid moieties [13]). Peptides consisting entirely of d-amino acids with proteinogenic side chains are completely stable towards peptidases; they are often used to study those properties of their normal counterparts (enantiomers!…”
mentioning
confidence: 99%
“…The specific type of gramicidin is determined by the 11th amino acid in the 15 amino acid sequence. For example, gramicidin A has the sequence [22,23] …”
Section: Methodsmentioning
confidence: 99%
“…The specificity of charging is of a lower order than that achieved by the nucleic acid-coded adaptor system of protein synthesis, as amino acid substitutions have been reported, for example, in tyrocidines"9 20 and gramicidins. 21 It was already reported that the fraction II enzyme catalyzes, in addition to ATP-PP032, an ATP-AMP exchange dependent on either L-or D-phenylalanine.1 This indication of a transfer of phenylalanine from adenylate to an unknown acceptor site is confirmed by the excess of bound phenylalanine over bound adenylate, while retaining carboxyl activation. The excess is equal to the amount of acyl adenylate when L-phenylalanine is used as a substrate or is much greater when D-phenylalanine is used.…”
mentioning
confidence: 86%